2020
DOI: 10.1021/acs.est.0c05397
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidation of Zero-Valent Iron by Direct Reaction with Elemental Sulfur in Water: Efficiencies, Mechanism, and Dechlorination of Trichloroethylene

Abstract: Sulfidation can enhance both the reactivity and selectivity (i.e., electron efficiency, εe) of zero-valent iron (ZVI) in contaminant removal, which may make this technology cost-effective for a wider range of water treatment applications. However, current sulfidation methods involve either hazardous or unstable sulfidation agents (e.g., Na2S, Na2S2O3, and Na2S2O4) or energy-intensive preparations (e.g., mechanochemical sulfidation with elemental sulfur). In this study, we demonstrate that very efficient sulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(23 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The shell was comprised predominantly of iron sulfides (FeS or FeS 2 ) and iron oxides (Fe 2+ -O). Subsequent studies adopted or modified the method by Xu et al, making it the most common approach for the synthesis of S-mZVI two‑step , and Na 2 S the preferred sulfidation agent, though other sulfur sources are gaining popularity (e.g., S 0 and Na 2 S 2 O 3 ). ,,, , …”
Section: Synthesis Methods and Its Impacts On S-nzvi Composition And ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The shell was comprised predominantly of iron sulfides (FeS or FeS 2 ) and iron oxides (Fe 2+ -O). Subsequent studies adopted or modified the method by Xu et al, making it the most common approach for the synthesis of S-mZVI two‑step , and Na 2 S the preferred sulfidation agent, though other sulfur sources are gaining popularity (e.g., S 0 and Na 2 S 2 O 3 ). ,,, , …”
Section: Synthesis Methods and Its Impacts On S-nzvi Composition And ...mentioning
confidence: 99%
“…Xu et al found that the iron (Fe 2+ , Fe 3+ ) and sulfur precursors (Na 2 S 2 O 4 , Na 2 S, and K 2 S 6 ) used for synthesis significantly affect the performance of nZVI and S-nZVI for the degradation of TCE, which may contribute to the large variability in reactivity observed among different studies. In addition, ball milling , or post synthesis with elemental sulfur seems to be superior sulfidation methods for the degradation of TCE with reported R values larger than 100, albeit with limited data available.…”
Section: Contaminant Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…One compelling solution to tackle these problems is through the deployment of microscale zero‐valent iron (mZVI), which is one of the most important multifunctional environmental remediation materials owing to its low cost, high abundance, and environmental benignity. [ 2 ] mZVI bears a captivating core‐shell structure, featured by an iron oxide layer containing abundant rich Lewis acid or base sites for heavy metal ion complexation, and an iron core acting as an electron reservoir (Fe(II)/Fe(0), −0.44 V versus SHE) towards reductive heavy metal immobilization. [ 3 ] Moreover, the solid‐liquid separation property of mZVI when subject to magnetic fields makes it reliable for in situ remediation, as well as effortless recycling without producing secondary pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, nZVI particles have a number of limitations that affect their reaction with contaminants: (1) nZVI easily aggregate based on the action of van der Waals force and magnetic force, and eventually reduce the migration in aquifer (Phenrat et al 2007;Israelachvili et al 2008;Li et al 2017). (2) nZVI particles with extremely high reactivity can react with other substances in the water besides the target contaminants, resulting in poor selectivity for pollutants (Cai et al 2020;He et al 2020). (3) When using nZVI in practice, a passivation layer can be easily to form on the surface of nZVI prohibiting Fe 0 core to react with pollutants, thus lower the reactivity (Sarathy et al 2008).…”
Section: Introductionmentioning
confidence: 99%